Urgan. - Catteau, Manuel; Bigot, Philippe; Glowacki, Corinne; Forrest, Jodie (Paris, France : ZED, 2006)
Life is not always taught on school benches. In many countries, children must first learn ancestral traditions and know-hows. This series invites kids to travel the world and discover other lifestyles and ways of growing up. Each episode features a different child who is initiated by an elder to a special task in which he will have to demonstrate courage and maturity.
Title from resource description page (viewed Feb. 27, 2013).
Previously released as DVD.
This edition in English.
Keywords: Coming of age -- China -- Tibet Autonomous Region; Initiation rites -- China -- Tibet Autonomous Region; Children -- China -- Tibet Autonomous Region; Buddhist monks -- China -- Tibet Autonomous Region; Tibet Autonomous Region (China) -- Rites and ceremonies; Nonfiction films